Hydrotropic Solubilization in Pharmaceutical Analysis: Origin, Evolution, Cumulative Trend and Precise Applications. (7th May 2021) - Patil, Mangesh R.; Ganorkar, Saurabh B.; Patil, Amod S.; Shirkhedkar, Atul A.; Surana, Sanjay J.
Abstract: The hydrotropy though existing as precisely used scientific approach assisting solubilization for all. It took 66 long years to use the concept in drug analysis since its inception in 1916 and first use for facilitation of drug solubility toward better pharmaceutical analysis in 1982. Considering the unending importance in pharmaceutical sciences and thereby in analysis, it's a necessity to comprehensively outlook the origin, evolution, cumulative trend and precise applications in pharmaceutical analysis. Achieved hereby with chronological and comparative assessment of the studies published pertaining to solubility enhancement of poorly soluble drugs with use of hydrotropic agents alone or in combination for assisting pharmaceutical analysis. The thorough literature searches resulted into 77 references over a span of about 38 years. This comprehensive review critically evaluates existing literature; to our surprise we found Ibuprofen sodium, Lignocaine, Niacinamide and Metformin HCl as atypical hydrotropic agents. We also compared herein mono and mixed approaches which indicated prevalence of mono - hydrotropy over mixed. The possible mechanisms behind solubilization are presented for an additional insight. An essential effort has been made to state arbitrary classification to assist in future applications. The obvious purpose of this study was to collectively evaluate the crucial role of hydrotropic agents in pharmaceutical analyses for better drug delivery. This comprehensive review covers all details since inception to the updates till date which will definitely act as appropriate guideline for pharmaceutical analyst's in need of hydrotropy to assist pharmaceutical analysis for therapies today and tomorrow.